Feasibility of recording EEG in the ambulance using a portable, wireless EEG recording system. - Sampsa Lohi; Pekka Jäkälä; Jouni Kurola; Pasi Tuunanen; Susanna Westeren-Punnonen; Anu Muraja-Murro; Reetta Kälviäinen; Esa Mervaala (PLoS ONE, 2025)
Objective Triaging acute ischemic stroke patients is difficult in prehospital settings. We investigated if a quickly applicable and compact EEG recording system is usable for stroke patients in the ambulance. Methods The EEG of 10 acute stroke patients from Kuopio University Hospital, Finland was recorded using a forehead EEG electrode set and compact EEG amplifier-recorder during their ambulance transfer to another healthcare facility. The recordings were transmitted wirelessly in real time to our server, and their quality and the interruptions and technical difficulties in the wireless data transfer were analysed. Results In 9 of the 10 recordings, the signal quality was sufficient for interpreting at least half of the recording. The signal quality suffered from artefacts caused by the patients' movements and the loosening of the electrode contacts. Only 50-Hz AC artefacts that affected the reference electrode were considered obtrusive and required digital filtering in two recordings. Conclusions We demonstrated that adequate-quality EEG can be recorded in an ambulance using a quickly applicable and compact recording system and reliably transferred to a remote server for real-time review. Significance This system can be used to measure EEG in acute indications in the prehospital setting.